2002
DOI: 10.1073/pnas.162354599
|View full text |Cite
|
Sign up to set email alerts
|

Mistargeting hippocampal axons by expression of a truncated Eph receptor

Abstract: Topographic mapping of axon terminals is a general principle of neural architecture that underlies the interconnections among many neural structures. The Eph family tyrosine kinase receptors and their ligands, the ephrins, have been implicated in the formation of topographic projection maps. We show that multiple Eph receptors and ligands are expressed in the hippocampus and its major subcortical projection target, the lateral septum, and that expression of a truncated Eph receptor in the mouse brain results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 51 publications
2
54
0
Order By: Relevance
“…Among them are Epha6, a tyrosine kinase receptor important for axon guidance, as well as Slc5a7, which encodes choline transporter responsible for proper choline uptake along the synapse. 18,19 Eleven genes are associated with cellular development/ death ( Figure 1c). Among them, downregulation of Mc1r and downregulation of Glra1 are two examples that show functional relevance to AS.…”
Section: Pathway Analysismentioning
confidence: 99%
“…Among them are Epha6, a tyrosine kinase receptor important for axon guidance, as well as Slc5a7, which encodes choline transporter responsible for proper choline uptake along the synapse. 18,19 Eleven genes are associated with cellular development/ death ( Figure 1c). Among them, downregulation of Mc1r and downregulation of Glra1 are two examples that show functional relevance to AS.…”
Section: Pathway Analysismentioning
confidence: 99%
“…EphARs are also critical in establishing topographically organized hippocampal-septal projections (Yue et al, 2002). There is considerable evidence that activation of EphB receptors regulates the structure and function of excitatory synapses in the hippocampus (Dalva et al, 2000;Grunwald et al, 2001;Penzes et al, 2003).…”
Section: Synapse Wrappingmentioning
confidence: 99%
“…The function of the EphA5 receptor is best characterized as an axon guidance molecule during neural development (Cheng et al, 1995;Yue et al, 2002). The EphA5 receptor and its ligand act as a repellant cue that prevents axons from entering inappropriate territories, thus restricting the cells to specific pathways during the migratory process (Wilkinson, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that this interaction causes inhibition of the neurite outgrowth of hippocampal, striatal, retinal, and cortical neurons, while it enhances the neurite outgrowth of sympathetic neurons and stimulates neurite sprouting of cortical neurons in vitro (Brownlee et al, 2000;Gao et al, 2000Gao et al, , 1998aGao et al, , 1996. At the circuit level, overexpression of a truncated form of EphA5 receptor resulted in a miswiring of the hippocamposeptal pathway and corpus callosum connections in vivo (Yue et al, 2002). In particular, medial hippocampal neurons with high expression level of the EphA5 receptor projected to both the ventral and lateral part of the target site while lateral hippocampal neurons with relatively low EphA5 receptor expression did not exhibit any obvious alteration in their projection pattern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation